Maternal alcohol consumption during pregnancy and associated factors among pregnant women in Tanzania: evidence from the 2022 Tanzania Demographic and Health Survey - Victoria Godfrey; Elihuruma Eliufoo; Immaculata P. Kessy; Mussa Bago; Mtoro J. Mtoro; Azan Nyundo (BMC Pregnancy and Childbirth)
Abstract Background Maternal alcohol consumption remains a significant public health concern. The consumption is associated with an increased risk of miscarriage, stillbirth, and Fetal Alcohol Spectrum Disorders, which can impair fetal growth and lead to low birth weight. This study aims to investigate the prevalence of alcohol use among pregnant women and identify associated factors utilising data from the 2022 Tanzania Demographic and Health Survey and Malaria Indicator Survey (TDHS-MIS). Methods This analytical cross-sectional survey design utilised secondary data from the 2022 TDHS-MIS. The survey employed a multistage cluster sampling method to generate representative national and sub-national health and health-related indicators between February and July 2022. A total of 1,182 pregnant women were included in the analysis. Data analysis involved descriptive statistics and binary logistic regression using STATA version 18.5 to assess factors associated with maternal alcohol consumption. Adjusted odds ratios (aOR) with 95% confidence intervals (CI) were computed to estimate the strength of the association between independent variables and alcohol use. Results The mean age of the participants was 27.3 years (standard deviation: 6.9). The overall prevalence of alcohol consumption during pregnancy among pregnant women in Tanzania was 3.9% (95% CI: 2.8–5.4). Factors associated with alcohol consumption were women aged 25–34 (aOR = 5.17, 95%CI: 1.62–16.51) and more than 35 years of age (aOR = 20.89, 95%CI: 6.55–66.62), women who were never married (aOR = 7.89, 95%CI: 2.20-28.25), On the other hand, women living in the western zone (aOR = 0.20, 95%CI: 0.04–0.88). Conclusion The study reveals a notable prevalence of alcohol consumption during pregnancy in Tanzania. Key demographic factors influencing alcohol use include maternal age, marital status, and prominent regional disparities, notably lower rates in Zanzibar compared to the western zone. These findings highlight the necessity for targeted public health initiatives to educate pregnant women. This was a cross-sectional survey, which limited the causal relationship among the observed factors.